Development of improved foot-and-mouth disease (FMD) assays with a focus on small ruminants in southern Africa - Fosgate, Geoffrey Theodore (University of Pretoria, 2025)
Thesis (PhD (Production Animal Studies))--University of Pretoria, 2024.